Membangun Minat dan Motivasi Belajar Sains Melalui Pengenalan Praktikum di SMPN 2 Jonggat - Nina Nisrina; Joni Rokhmat; kosim kosim; sutrio sutrio; Jannatin 'Ardhuha (Jurnal Pengabdian Pendidikan IPA Kontekstual, 2025)
This community service activity aimed to enhance students' interest and motivation in learning science through the introduction of hands-on science practicum. The activity involved 21 seventh-grade students of SMPN 2 Jonggat, Central Lombok Regency. The materials introduced included fluids, Newton's laws, Pascal's law, static electricity, dynamic electricity, and waves. The program was carried out through a series of interactive sessions, including conceptual introduction, demonstration, and simple group-based experiments. The results showed that students demonstrated high enthusiasm, asked more questions, and reported greater interest in science after participating in the activity. Evaluation through a simple questionnaire indicated a positive increase in students' learning interest and motivation. This activity proved that simple and contextual science practicum can be an effective approach to enrich science learning, especially in schools with limited laboratory facilities.